Penerjemahan Frasa Verbal dari Bahasa Inggris ke Bahasa Indonesia - NFN Engliana; Ira Miranti (Ranah: Jurnal Kajian Bahasa, 2020)
This research analyzes the translation of English phrasal verbs into Indonesian. The goal of this research is to identify the translators’ understanding by means of equivalent translation of the phrasal verbs in Indonesian. Such goal is valuable since it helps us to see how the translators were able to comprehend meanings in context. The translation results also enable us to recognize the translators’ understandings of phrasal verbs of source language and their meanings in target language. This is a qualitative research which employs content analysis method. The data analysis technique is categorizing, or separation of the translation results based on the source language’s phrasal verbs type prior to applying meaning equivalence principles to the translations. The results of the analysis show that the respondents still face difficulties in translating English phrasal verbs into Indonesian because they are fixated on the verbal structures of source language and lack of understanding of the rules of the source language structure (linguistic barrier). Metacognitive barrier plays a role in the translation process due to lack of background knowledge gained from experience, thus affecting the ability to build strategies and influence decision-making.AbstrakPenelitian ini menganalisis penerjemahan frasa verbal dari bahasa Inggris ke bahasa Indonesia. Tujuan dari penelitian ini adalah mengidentifikasi pemahaman penerjemah melalui kesepadanan makna frasa verbal bahasa Indonesia. Usaha identifikasi ini bermanfaat untuk mengenali bahwa pemahaman makna kombinasi frasa verbal bahasa sumber dan konteks penggunaan frasa verbal dalam kalimat dapat diserap dengan baik oleh penerjemah sehingga dapat menghasilkan terjemahan yang tepat. Penelitian ini didasarkan pada pendekatan kualitatif, yaitu menggunakan metode kajian isi. Teknik analisis data menggunakan kategori atau pemisahan hasil terjemahan berdasarkan jenis frasa verbal bahasa sumber, kemudian kriteria kesepadanan makna diterapkan pada hasil terjemahan. Hasil analisis menunjukkan bahwa para responden masih menghadapi kesulitan menerjemahkan frasa verbal bahasa Inggris ke bahasa Indonesia karena mereka masih terpaku pada struktur frasa verbal bahasa sumber dan kurang memahami kaidah struktur bahasa sumber (linguistic barrier). Didapati juga metacognitive barrier, yaitu kurang latar belakang pengetahuan yang diperoleh dari pengalaman sehingga mempengaruhi kemampuan membangun strategi dan memengaruhi pengambilan putusan.